Pengaruh Metode The Power Of Two Terhadap Hasil Belajar Siswa pada Mata Pelajaran Bahasa Indonesia Kelas IV SD Negeri 067240 Medan T.P 2024/2025 - Anggi Fajariani; Faisal Faisal; Halimatussakdiah Halimatussakdiah; Lala Jelita Ananda; Edizal Hatmi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study aims to determine whether there is an influence of the Power of Two method on the learning outcomes of fourth grade students of SD Negeri 067240 Medan in the academic year 2024/2025. This study is a quantitative study with a Quasi Experimental Design research type in the form of Nonequivalent Control Group Design. The sample of this study was 13 students of class IV A and 13 students of class IV B. The instrument used was a multiple choice test. This research technique uses the t-test statistical method. The results of data analysis show that the average learning outcomes using The Power of Two method in the experimental class is 82.69, while the average learning outcomes not using The Power of Two method in the control class is 70. In the normality test with the provision that if sig > 0.050 it is known that the results of the pre-test and post-test of the experimental class and the control class are normally distributed with the acquisition of values ​​in the experimental class pre-test, test results = 0.433 > 0.050 and in the post-test results, test results = 0.227 > 0.050 while in the control class pre-test, test results = 0.155 > 0.050 and in the post-test results, test results = 0.487 > 0.050. The results of the homogeneity test of the research data, it is known that the research data comes from homogeneous samples with the acquisition of homogeneity test values ​​in the pre-test and post-test obtaining significant values, namely 0.758 and 0.325, which means more than 0.050 (Sig.> 0.050), then it can be concluded that both data are said to be homogeneous. Data analysis with hypothesis testing using the independent sample t-test with a significance level of α = 0.05 and degree of freedom (df) = 24. From the results of the hypothesis test, tcount> ttable (5.500> 2.308) or H0 is rejected and H1 is accepted. So it can be stated that there is a significant influence between the application of the Power of Two method on the learning outcomes of grade IV students of SD Negeri 067240 Medan Academic Year 2024/2025